Geographical, Climatological, and Biological Characteristics of Tree Radial Growth Response to Autumn Climate Change - Tei, Shunsuke; Kotani, Ayumi; Sugimoto, Atsuko; Shin, Nagai (Frontiers in Forests and Global Change, 2021)
Terrestrial forest ecosystems are crucial to the global carbon cycle and climate system; however, these ecosystems have experienced significant warming rates in recent decades, whose impact remains uncertain. This study investigated radial tree growth using the tree-ring width index (RWI) for forest ecosystems throughout the Northern Hemisphere to determine tree growth responses to autumn climate change, a season which remains considerably understudied compared to spring and summer, using response function and random forest machine learning methods. Results showed that autumn climate conditions significantly impact the RWI throughout the Northern Hemisphere. Spatial variations in the RWI response were influenced by geography (latitude, longitude, and elevation), climatology, and biology (tree genera); however, geographical and/or climatological characteristics explained more of the response compared to biological characteristics. Higher autumn temperatures tended to negatively impact tree radial growth south of 40° N in regions of southern Europe, the United States of America, and Mexico, which was similar to the summer temperature response found in previous studies, which was attributed to temperature-induced water stress.